Responsividade: um levantamento sobre as práticas responsivas nas empresas de confecção femininas de Fortaleza - Rodrigues, Aline da Silva (2012)
This dissertation aimed to survey the practices undertaken by companies responsive clothing women's Fortress. To achieve the main objective, we sought to determine whether the companies could be considered responsive, and whether they could be classified as entrepreneurial business model of fast fashion. For this survey, we developed a questionnaire with closed questions taken from the literature on responsiveness and fast fashion. Associated companies were selected to SindConfecções. Data were analyzed analytically and concluded that the companies surveyed do not think are responsive and can be neither quick fashion, not to undertake the main principles of responsiveness, nor the most constant of fast fashion. Thus, it can also be concluded that the practices are not responsive undertaken by such enterprises, hindering the development of the model of fast fashion.